ETHICAL AND LEGAL ASPECTS OF INFECTIOUS DISEASES AND VACCINATION. Part 2. Ethical aspects of planning and conducting of research in the field of vaccine prevention - O. I. Kubar (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The current article continuing the presentation of data on ethical, legal and social aspects of problems connected with the studies for prevention of infectious diseases. In the frame of this article the international conception of research in the vaccine prevention field has been presented. The legal component of ethical principles during conducting studies of immunobiological preparations in the Russian Federation has been demonstrated.